100 Unintended consequences of policies to improve the energy efficiency of the UK housing stock. Issue 3 (May 2014) - Shrubsole, C.; Macmillan, A.; Davies, M.; May, N.
As a major sector contributing to the UK's greenhouse gas (GHG) emissions, housing is an important focus of government policies to mitigate climate change. Current policy promotes the application of a variety of energy efficiency measures to a diverse building stock, which will likely lead to a wide range of unintended consequences. We have undertaken a scoping review identifying more than 100 unintended consequences impacting building fabric, population health and the environment, thus highlighting the urgent need for government and society to reconsider its approach. Many impacts are connected in complex relationships. Some are negative, others possibly co-benefits for other objectives. While there are likely to be unavoidable trade-offs between different domains affected and the emissions reduction policy, a more integrated approach to decision making could ensure co-benefits are optimised, negative impacts reduced and trade-offs are dealt with explicitly. Integrative methods can capture this complexity and support a dynamic understanding of the effects of policies over time, bringing together different kinds of knowledge in an improved decision-making process. We suggest that participatory systems dynamics with multi/inter-disciplinary stakeholders is likely to offer a useful route forward, supporting cross-sectorial policy optimisation that places reducing housing GHG emissions alongside other housing policy goals.